One day and one amazing morning on Orange Street - Rocklin, Joanne (New York : Amulet Books, 2011)
The last remaining orange tree on a Southern California street brings together neighbors of all ages as they face their problems and anxieties, including the possibility that a mysterious stranger is a threat to their tree.
Kirkus Starred
Publisher's Weekly
Kirkus Starred, March 2011
Publisher's Weekly, February 2011
Young Adult
Young Adult
Keywords: Families -- California -- Juvenile fiction; Friendship -- Juvenile fiction; Neighborhoods -- Juvenile fiction; Oranges -- Juvenile fiction; Trees -- Juvenile fiction; Family life -- California -- Fiction; Friendship -- Fiction; Neighborhoods -- Fiction; Oranges -- Fiction; Trees -- Fiction; Family life -- California -- Fiction; Friendship -- Fiction; Neighborhoods -- Fiction; Oranges -- Fiction; Trees -- Fiction; California -- Juvenile fiction; California -- Fiction; California -- Fiction